The Role of Melanocortin Plasticity in Pain-Related Outcomes After Alcohol Exposure - Sharfman, Nathan; Gilpin, Nicholas W. (Frontiers in Psychiatry, 2021)
The global COVID-19 pandemic has shone a light on the rates and dangers of alcohol misuse in adults and adolescents in the US and globally. Alcohol exposure during adolescence causes persistent molecular, cellular, and behavioral changes that increase the risk of alcohol use disorder (AUD) into adulthood. It is established that alcohol abuse in adulthood increases the likelihood of pain hypersensitivity and the genesis of chronic pain, and humans report drinking alcohol to relieve pain symptoms. However, the longitudinal effects of alcohol exposure on pain and the underlying CNS signaling that mediates it are understudied. Specific brain regions mediate pain effects, alcohol effects, and pain-alcohol interactions, and neural signaling in those brain regions is modulated by neuropeptides. The CNS melanocortin system is sensitive to alcohol and modulates pain sensitivity, but this system is understudied in the context of pain-alcohol interactions. In this review, we focus on the role of melanocortin signaling in brain regions sensitive to alcohol and pain, in particular the amygdala. We also discuss interactions of melanocortins with other peptide systems, including the opioid system, as potential mediators of pain-alcohol interactions. Therapeutic strategies that target the melanocortin system may mitigate the negative consequences of alcohol misuse during adolescence and/or adulthood, including effects on pain-related outcomes.